Real‐world experience of suture‐based closure devices: Insights from the FDA Manufacturer and User Facility Device Experience. Issue 3 (4th February 2021) - Case, Brian C.; Kumar, Sant; Yerasi, Charan; Forrestal, Brian J.; Musallam, Anees; Chezar‐Azerrad, Chava; Khalid, Nauman; Shlofmitz, Evan; Chen, Yuefeng; Khan, Jaffar M.; Satler, Lowell F.; Ben‐Dor, Itsik; et al.
Abstract: Objectives: We analyzed post‐marketing surveillance data from the United States Food and Drug Administration (FDA) Manufacturer and User Facility Device Experience (MAUDE) database for suture‐based vascular closure devices (VCDs) – Perclose ProGlide (Abbott, Chicago, Illinois) and Prostar XL (Abbott). Background: Suture‐based VCDs are mostly used for large‐bore femoral arterial access‐site closure. Real‐world, contemporary experience on the most commonly reported complications and modes of failure associated with these devices is limited. Methods: Post‐marketing surveillance data from the FDA MAUDE database, for the ProGlide system and for the Prostar XL system, were analyzed, yielding 827 Perclose ProGlide reports and 175 Prostar XL reports. Results: Of the 827 reports of major complications involving the Perclose ProGlide devices, 404 reports involved injury, and one involved death related to the device. In the Prostar XL analysis, 94 reports involved injury, and one involved death. Bleeding from vessel injury was the most common adverse outcome described with both devices, followed by hematoma and thrombus. Surgical repair was the most commonly used treatment strategy. In terms of device malfunction, suture‐related malfunction (212 reports) was most commonly seen in the Perclose ProGlide group, while failed deployment was most commonly seen in the Prostar XL group. Conclusions: Our analysis of the MAUDE database demonstrates that in real‐world practice, suture‐based VCDs were found to be associated with complications, including vascular injury, difficulties with the device itself, and even death. Ongoing user education and pre‐procedural patient selection are important to minimize risks associated with suture‐based vascular closure devices.